Motivación y su influencia en el desempeño laboral de la Compañía Radio Fluminense S.A. “RADFLUMINSA - Moreira Carrera, Isabel Del Rocío (2017)
Motivation is currently important in companies because it is a significant element for employees to feel satisfied and have an excellent job performance, a major factor in the performance of their work activities in order to achieve the proposed goals and objectives, and thus have the staff to carry out their tasks with dedication and achieve greater productivity, in organizations the motivation can be carried out in different ways, with the aim of the employees render and maximize their performance in the area of ​​work